Acute Physiological and Metabolic responses for 40-minutes of Samba Dance - Santos-Silva, Paulo R.; Duarte, Cicera C.; Osorio, Bruna B.; Greve, Julia Maria D.A.; Guimaraes, Guilherme V. (Open Science Journal, 2021)
Dance is an enjoyable health-promoting physical activity that many people worldwide incorporate into their lifestyles today. Therefore, dance improves your heart health, overall muscle strength, balance, and coordination, and reduces depression. We aim to gain insights into the effects of samba dance on the cardiorespiratory and metabolic response during an acute session of this dance style for 40-minutes. The study was carried out on 20 female samba dancers. All of them performed two procedures: (1) a cardiopulmonary exercise test on a treadmill for physical fitness aptitude verification and (2) a 40-minutes of samba dancing monitored by analysis of expired gases. The results were: At peak exercise: oxygen uptake (VO2) =32.7 mL.kg-1.min-1; heart rate (HR) =183 bpm; the pulse of oxygen (PO2) =10.9 mL.HR-1, energy expenditure (EE) = 9.9 kcal.min-1and metabolic equivalent (METs)=13.5.Overall, each session of the dance of 40-minutes was performed at a mean VO2 of 22.8 mL.kg-1.min-1 (70%VO2max), heart rate of 162 bpm (89%HRmax), energy expenditure (EE) of 6.5 kcal.min-1 (66%max), metabolic equivalent (METs) of 6.3 (62%max), and the rate of perceived exertion (RPE) of 11.8/20. In conclusion: The findings of the current investigation might suggest that the moderate and vigorous-intensity of the exercise verified in an acute samba dance session is enough to induce a chronic training effect recommended by the criteria established by the American College of Sports Medicine for improving cardiorespiratory fitness. This information may lead to a better understanding of the energy expenditure of samba dance and add to the compendium of physical activity.